KONTROL NEGARA ATAS TUBUH PEREMPUAN: PRO KONTRA RUU ANTIPORNOGRAFI DAN PORNOAKSI PADA MASYARAKAT KOTA SEMARANG - Lestari, Puji (Faculty of Social Science, Universitas Negeri Semarang, 2009)
Indonesian state, with the culture of patriarchy inherent in community life, always put women inÃ‚Â positions that are diffcult and cornered. With his power, often state that does not make policy genderÃ‚Â sensitive. Including today, where the bill becomes law product APP disturbing for some people. ThisÃ‚Â study raised Ã‚Â the Ã‚Â issue about How Semarang citizen opinion about Ã‚Â the Pornoaction and pornography?Ã‚Â How Semarang citizen opinion about the content of RUU APP and position of women in society? WhatÃ‚Â factors are inhibiting the implementation of the bill into law APP? The purpose of this study was toÃ‚Â determine public opinion of the Semarang citizen about Pornoaction and pornography, knowing the publicÃ‚Â opinion of the Semarang citizen about the content of bill APP and the position of women in society andÃ‚Â what factors are inhibiting the implementation of the bill into law APP. The results of this study is theÃ‚Â emergence of the Draft Law on Anti-pornography and Pornoaction, provides an illustration of the growingÃ‚Â infuence of the state to the womenÃ¢â‚¬â„¢s bodies. This led to a public anxiety about the position of women isÃ‚Â increasingly cornered. Pros and cons of the contents of the Bill of APP caused by multiple interpretationsÃ‚Â of the contents of the articles RUU APP. In addition, also due to the assessment and perspectives ofÃ‚Â different communities about the content of this RUU APP. Community pro Semarang RUU APP arguesÃ‚Â that the existence of RUU APP can protect the nation from moral destruction, especially for the youngerÃ‚Â generation. While that does not agree with the existence of this bill due to cultural differences, as wellÃ‚Â as the position of women that are cornered.Keywords: Pornography, Pornoaction